IMPACT OF ORGANICS ON LEAF SPOT COLLETOTRICHUM DISEASE AND RHIZOME YIELD OF TURMERIC (Journal of Plant Disease Sciences, 2017)
Turmeric ( L.)is Curcuma longa highly prone to several fungal diseases, among them major fungal disease is leaf spot incited by (Syd.) Colletotrichum capsici Butler & Bisby causing fresh rhizome yield loss to the tune of 15-60% (Pruthi, 1998) and dry rhizome yield 62% approximately. The disease was first reported from Coimbatore district by Mc Rae in 1917 (Ramakrishnan, 1954). It is more severe in southern states (Gomathi, 2001) but caused heavy yield loss in Uttar Pradesh (Mishra and Pandey, 2014).The application of chemical fungicides are producing hazardous consequences in term of soil pollution, reducing the quality of arable land and ground water (Bezbaruah, 2000) and bio-pesticides are usually inherently less toxic than conventional pesticides (Singh, 1999). They generally affect only the target pathogenic organism, in contrast to broad spectrum fungicides. Fresh plant extracts from different plant parts are becoming valuable for management of the pathogens, which can be easily prepared by farmers. Cow's urine is an important constituent of Panchgavya and is used in several Panchgavya formulations (Okigbo and Nameka, 2005). Cow's urine based Nigerian herbal formulation were prepared with the use of several herbs like tobacco, garlic, lemon juice and bulbs of onion. These herbal formulations have been described for the use in medicinal and agricultural applications. (Fulzele , 2001). Keeping in et al view, fieldstudies were carried out to select suitable management practices for reducing the leaf spot disease of turmeric. The trial was conducted under field condition at vegetable farm, Narendra Deva University of Agriculture and Technology Kumarganj Faizabad during 2013-14 in sandy
Keywords: Turmeric, cow's urine, leaf spot, management Colletotrichum capsici